Pemberdayaan masyarakat dalam pengembangan wisata Waduk Wadaslintang dengan membangun komunitas pecinta waduk di Kabupaten Wonosobo - Andriawan, Aan; Yasinta, Syaukaty; Dungga, Yunus Renato; Mustofa, Arya; Putra, Firli Sucia (Penamas: Journal of Community Service, 2025)
The Wadaslintang Dam is located in Sumberejo Village, Wadaslintang District, Wonosobo Regency, and borders Padureso District, Kebumen Regency, Central Java Province, along the Bedegolan River within the Serayu–Bogowonto River Basin. Known for its stunning natural beauty, the reservoir holds significant potential as an attractive tourist destination. The vision of this community engagement program is to develop Wadaslintang Reservoir into a leading tourism site that is community-managed, sustainable, and capable of empowering the local population. The program employed methods of socialization and mentoring, supported by a series of initiatives that actively involved the community, including awareness-raising through reflective discussions, the establishment of reservoir enthusiast groups, participatory mapping, and long-term participatory planning. The activities enhanced community understanding of their vital role in reservoir management, as shown by evaluation results, where the average pre-test score of 63.33 increased to 85.33 out of 100 in the post-test following the socialization activities. This improvement highlights the effectiveness of participatory approaches and two-way communication in fostering community awareness and engagement.